Impact of macroeconomic variables on foreign exchange reserves: A case from Pakistan - Muhammad Azeem; Muzammil Khurshid (Universitas Islam Indonesia, 2019)
The study aims to investigate the effect of macroeconomic indicators on foreign reserves in Pakistan. A Vector Autoregressive (VAR) model has been used to estimate Pakistan’s foreign exchange reserves demand from the period of 1984 to 2015. Findings/Originality: The results indicate that macroeconomic variables such as remittances, exchange rate, the ratio of current account deficit to GDP and interest rate differential (measure as opportunity cost) determine the country’s long-run reserves demand function. Whereas, observed results show that demand of foreign reserves is highly sensitive to capital account vulnerability and less responsive to its opportunity cost. The Granger causality analysis shows that the various macroeconomic variables fail to cause reverse causality. It implies that in Pakistan the demand of reserves is driven by macroeconomic stability. The study is helpful for the country’s institutions to boost foreign reserves by controlling macroeconomics indicators.